MR‐guided pulsed focused ultrasound improves mesenchymal stromal cell homing to the myocardium. Issue 22 (17th October 2020) - Jang, Kee W.; Tu, Tsang‐Wei; Rosenblatt, Robert B.; Burks, Scott R.; Frank, Joseph A.
Abstract: Image‐guided pulsed focused ultrasound (pFUS) is a non‐invasive technique that can increase tropism of intravenously (IV)‐infused mesenchymal stromal cells (MSC) to sonicated tissues. MSC have shown promise for cardiac regenerative medicine strategies but can be hampered by inefficient homing to the myocardium. This study sonicated the left ventricles (LV) in rats with magnetic resonance imaging (MRI)‐guided pFUS and examined both proteomic responses and subsequent MSC tropism to treated myocardium. T2‐weighted MRI was used for pFUS targeting of the entire LV. pFUS increased numerous pro‐ and anti‐inflammatory cytokines, chemokines, and trophic factors and cell adhesion molecules in the myocardial microenvironment for up to 48 hours post‐sonication. Cardiac troponin I and N‐terminal pro‐B‐type natriuretic peptide were elevated in the serum and myocardium. Immunohistochemistry revealed transient hypoxia and immune cell infiltration in pFUS‐targeted regions. Myocardial tropism of IV‐infused human MSC following pFUS increased twofold‐threefold compared with controls. Proteomic and histological changes in myocardium following pFUS suggested a reversible inflammatory and hypoxic response leading to increased tropism of MSC. MR‐guided pFUS could represent a non‐invasive modality to improve MSC therapies for cardiac regenerative medicine approaches.